2011
DOI: 10.1002/glia.21202
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of GABA release from human astrocytes

Abstract: We have previously demonstrated that human astrocytes are GABAergic cells. Throughout the adult human brain, they express the GABA synthesizing enzyme GAD 67, the GABA metabolizing enzyme GABA-T, and the GABA(A) and GABA(B) receptors. GABA modulates the actions of microglia, indicating an important role for astrocytes beyond that of influencing neurotransmitter function. Here we report on the mechanisms by which astrocytes release GABA. Astrocytes were found to express the mRNA and protein for multiple GABA tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 35 publications
1
72
0
Order By: Relevance
“…Various transmitters, such as L-glutamate, D-serine, GABA and kynurenic acid, are released from astrocytes (Hamilton and Attwell, 2010;Parpura and Zorec, 2010;Potter et al, 2010;Lee et al, 2011). Our previous study demonstrated that basal and 100 mM AMPA-evoked releases of L-glutamate and D-serine from astrocytes were inhibited by the glial toxin, FLC and the synaptobrevin inhibitor, TeNT, but such release was insensitive to the voltage-gated sodium channel inhibitor, TTX (Tanahashi et al, 2012), similar to the present results.…”
Section: Mechanisms Of Gliotransmitter Release In Cultured Astrocytessupporting
confidence: 90%
“…Various transmitters, such as L-glutamate, D-serine, GABA and kynurenic acid, are released from astrocytes (Hamilton and Attwell, 2010;Parpura and Zorec, 2010;Potter et al, 2010;Lee et al, 2011). Our previous study demonstrated that basal and 100 mM AMPA-evoked releases of L-glutamate and D-serine from astrocytes were inhibited by the glial toxin, FLC and the synaptobrevin inhibitor, TeNT, but such release was insensitive to the voltage-gated sodium channel inhibitor, TTX (Tanahashi et al, 2012), similar to the present results.…”
Section: Mechanisms Of Gliotransmitter Release In Cultured Astrocytessupporting
confidence: 90%
“…Because of the abundant expression of GABA receptors and GABA in the brain microenvironment (27), we investigated whether BBM cells had any GABAergic properties by comparing the expression of their genes and proteins to the highly passaged primary breast cancer cell lines, SkBr3 and MDA-MB-231. All GABA receptor mRNA isoforms were highly up-regulated in HER2…”
mentioning
confidence: 99%
“…The GABA transporter GAT-3 is exclusively expressed in astrocytes (Minelli et al 1996); GAT-1 and -2 are found in astrocytic processes and other neuronal-and nonneuronal elements (Conti et al 1998(Conti et al , 1999. As a result of the concerted action of these enzymes and transporters, cultured human astrocytes maintain an intracellular GABA level of 2.32 mM (Lee et al 2011b). On the same line, cultured human microglia express the mRNA and protein for GABA-T, in Fig.…”
Section: Discussionmentioning
confidence: 99%